Encapsulation of Pseudomonas aeruginosa elastase inside the P22 virus‐like particle for controlling enzyme–substrate interactions. Issue 9 (11th June 2022) - Patterson, Dustin; Draper, Derek; Anazia, Kara; Hjorth, Christy; Bird, Jessica; Fancher, Shandis; Azghani, Ali
Abstract: Controlling interactions between enzymes and interaction partners, such as substrates, is important for applications in cellular biology and molecular biochemistry. A strategy for controlling enzyme access with substrate interaction partners is to exploit encapsulation of enzymes inside nanoparticles to limit the accessibility of the enzymes to large macromolecules, but allow free exchange of small‐molecule substrates. The research here evaluates the encapsulation of Pseudomonas aeruginosa elastase inside the bacteriophage P22 virus‐like particle (VLP) to examine the ability to allow free soluble substrates access to the enzyme while blocking large macromolecular substrate interactions. The results show that the active elastase protease can be encapsulated inside the P22 VLP, which blocks its ability to disrupt cell monolayers, but allows soluble substrates to be catalytically cleaved, supporting the viability of this approach for future investigations. Graphical Abstract and Lay Summary: The research outlined in the article provides a proof‐of‐concept for utilizing virus‐like particle (VLP) and protein cage nanoparticles for investigating the substrate interactions of enzymes that might be involved in complex cellular interactions. By encapsulating enzyme inside the P22 VLP, we show that soluble substrates can diffuse through the 2‐4 nm pores in the VLP structure and be acted upon by the encapsulated enzyme, but larger insoluble and cellular substrates are prevented from being acted upon by the enzyme. These results indicate that encapsulation of enzymes inside of a virus‐like particle allows the potential for deciphering of small molecule vs. macromolecular cellular responses mediated by enzymes.